ANALISIS PERBANDINGAN KINERJA KEUANGAN MODEL ALTMAN DAN SPRINGATE PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B31112090, FRANSISCA GLATITIA (Jurnal Manajemen Update, 2016)
Financial distress is the decline stage of a company's financial condition. Companies experiencing financial difficulties in the long term have a tendency to go bankrupt. There are many people who will be harmed if a company went bankrupt, which is required for bankruptcy prediction models that can provide early warning for the company. The purpose of this study to determine whether there are differences in the comparison of financial performance using two prediction models for the financial performance and springate Altman models and to determine the most accurate predictive models in predicting companies experiencing delisting. The sample used is a mining company listed on the Stock Exchange during the period 2011-2014. The sampling technique is purposive sampling with the total sample were obtained as many as 15 companies. The criteria that must be met in a purposive sampling that is seen from companies that publish full financial statements in accordance with the needs of a period of years of research and is also seen not include other sectors moving company or do not include the information required in the study. Hypothesis testing using paired samples test then make predictions recap of calculating the level of accuracy and error of each model results to predict financial results. The results showed that 1) The financial condition of companies, mining samples in healthy condition is not in accordance with the predicted results. 2) There is a no difference significant financial performance comparison between the model predictions and Springate Altman. 3) Springate models are predictive model that has the best accuracy rate followed Altman Z-Score. Thus, it is advisable for the company while maintaining financial performance remains stable as it is now. Keywords : financial performance, the Altman model, The Springate model